Maternal age and origin of non-disjunction in trisomy 21. Issue 5 (October 1980) - Mattei, J F; Ayme, S; Mattei, M G; Giraud, F
Abstract : The role of maternal age in chromosomal non-disjunction was investigated by studying 51 families in whom the origin of the meiotic anomaly had been identified. Results of this study were compared with previously published data. This comparison did not show any difference in mean maternal age, nor in distribution of maternal ages when the origin of non-disjunction was maternal, or paternal, or occurred at the first or second meiotic division. These results make questionable the role of maternal age in the birth of Down's syndrome children.